(untitled) (American Journal of Arts and Human Science, 2024)
This paper examines the role of social media and mass media in political campaigns. It draws from a review of related studies/literature in an attempt to establish the vital role of social media and mass media in said campaigns. While the author did not utilize specific research methods in this research, a close examination of relevant literature on the subject matter has been conducted accordingly. The literature review underscores how the social media are increasingly utilized for political purposes. However, some authors note that politicians still depend on the traditional media for such purposes. While the traditional media remain as valuable vehicles of information in political campaigns, the social media are increasingly recognized as dynamic campaign tools. Along this line, in past campaigns in the U.S. and Brazil, the level of sophistication on how the social media were applied has been noted. As for other countries, the potentials of social media have yet to be harnessed and maximized since these primarily served as a platform for exchange between the candidates and the voters. Notably, televised election debates have been documented as the candidates’ crucial means of informing and persuading voters. Apparently, we have witnessed how these televised debates (as these are likewise streamed via YouTube) trigger discourse/exchange among citizens in the course of these debates. More importantly, in such discourse, the citizens themselves campaign for their chosen candidates.